A Point Prevalence Study Of Toxocariosis In Stray Cats In And Around Bhubaneswar, Odisha - Mahalik , Gautam (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A cross sectional study was conducted from April, 2012 to July, 2012 to determine the prevalence rate and influence of different risk factors on Toxocariosis in stray cats in and around Bhubaneswar, Odisha. The overall prevalence rate was found to be 56.2% with highest prevalence rate recorded in slum area (73%) followed by village area (52.1%) and least in urban area (33.3%) (P
Keywords: Prevalence rate; Toxocariosis; stray cats; Bhubaneswar